DEVELOPING WEB-BASED ONLINE TEST SYSTEM TO BOOST IELTS ACADEMIC READING SCORE - Hesti Rokhaniyah; Oddy Virgantara Putra (University of Kuningan, 2021)
Abstract: Web technology provides rich resources for both educators and learners in English teaching and learning process. In this context, the study aims at developing web-based online test for IELTS academic reading test on the users need for learners and educator of Universitas Darussalam Gontor. Addressing the issue of online test developing, this study utilized Alessi and Trollip instructional system design model. The formative evaluation and the increase in the average score at the pre-test and post-test of the learning motivation included alpha testing validated by two material and media experts and beta testing on learners’ attitude toward the online test, while summative evaluation covered learning outcomes. Upon analysis, the finding demonstrated that: (1) the resulting website: https://gets.unida.gontor.ac.id/pertanyaan/quiz was able to provide online evaluation for assessing reading performance among learners; (2) the increase in the average score on the pre-test and post-test of the learning outcomes of all learners was 0.43 (moderate category) and learner motivation scale was 0.38 (Medium-g courses). Hence, web-based online test could optimize learners’ excitement to assess their IELTS proficiency.